Penataan Artistik Pertunjukan Teater Dul Muluk Tunas Harapan di Palembang - Dedy Firmansyah; Nugroho Notosusanto Arhon Doni (Besaung : Jurnal Seni Desain dan Budaya, 2021)
Artistic arrangement is important in theater performances, as is Dul Muluk theater. "Decoration (scenery) is a background scene (background) where to play the play". Dul Muluk Theater is inseparable from the elements that support the show. The elements are divided into two parts, namely the main elements and supporting elements of the show. The main elements consist of: director, script, performer (actor / actress) and audience, while supporting elements of the show include: dress, property set, musical system, and stage decoration / decoration set. But in discussing this research journal, the writer discusses the supporting elements of his performance. The object of study in the research journal was the traditional arts group Dul Muluk Tunas Harapan, Pemulutan District, which was staged in Palembang. The theory used in this research journal is through Dramaturgi Harymawan's approach as grand theory. This type of research used in this research journal uses descriptive qualitative analysis. Data collection techniques carried out by observation, literature study, interviews, and documentation. The results of the research include; 1) Clothing that is useful to reinforce the character in accordance with the needs of the play, 2) Property as supporting elements of equipment in a theater performance, 3) Music Arrangement; apart from being a accompanist, illustrations, both as opening all the plays, opening scenes, giving effect to the play, and as a closing act also to give color and impression to the scene depicted on stage, 4) Tata Performances; the atmosphere of a place where the human soul can fly freely. A place where art is given breath.